University and sustainability: a theoretical approach for implementation (2015)
This paper aims to review the theoretical and instrumental aspects involved in the implementation of sustainability in universities as well as make a proposal for its management. Through the review of scientific literature on the relationship between sustainability and operational and substantive functions of universities, a logical-instrumental mechanism is proposed to put in place the components of sustainable development. The university environmental management system, the engagement of stakeholders as well as the use of teaching and research resources are proposed as stepping stones on the path allowing universities to move to sustainability. The paper provides a contribution in the area of sustainability for universities located in emerging countries by proposing an implementation model called “sustainable campus”.